2016
DOI: 10.1007/s00406-016-0710-9
|View full text |Cite
|
Sign up to set email alerts
|

The relationships of personal resources with symptom severity and psychosocial functioning in persons with schizophrenia: results from the Italian Network for Research on Psychoses study

Abstract: The relationships of personal resources with symptom severity and psychosocial functioning have never been tested systematically in a large sample of people with schizophrenia. We applied structural equation models to a sample of 921 patients with schizophrenia collected in a nationwide Italian study, with the aim to identify, among a large set of personal resources, those that may have an association with symptom severity or psychosocial functioning. Several relevant demographic and clinical variables were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 63 publications
5
34
1
Order By: Relevance
“…Since most of the patients used haloperidol and/or chlorpromazine in the present study, a lower dosage, rather than the use of atypical antipsychotics [68], seemed to be a key factor for better QoL. There were no correlations or significant differences between the socio-demographic factors and the CD-RISC-10 score; however, the patients with a paid occupation were more resilient according to the S-Qol 18 score, which was consistent with the results of previous studies [42,61,[66][67][68][69]. DUP, which affects QoL at the first visit to a medical institution [70], did not influence any QoL domains among our sample patient population who had already received psychiatric treatment.…”
Section: Plos Onesupporting
confidence: 90%
See 3 more Smart Citations
“…Since most of the patients used haloperidol and/or chlorpromazine in the present study, a lower dosage, rather than the use of atypical antipsychotics [68], seemed to be a key factor for better QoL. There were no correlations or significant differences between the socio-demographic factors and the CD-RISC-10 score; however, the patients with a paid occupation were more resilient according to the S-Qol 18 score, which was consistent with the results of previous studies [42,61,[66][67][68][69]. DUP, which affects QoL at the first visit to a medical institution [70], did not influence any QoL domains among our sample patient population who had already received psychiatric treatment.…”
Section: Plos Onesupporting
confidence: 90%
“…The results implied that lower social functioning did not necessarily equate to higher subjective QoL. The patients with paid occupations showed significantly better QoL scores, which led us to believe that the critical factor for better QoL is paid work, which is congruent with previous studies [42,61,[66][67][68][69]. As expected, patients with paid occupations showed lower PANSS-6 scores than those with unpaid occupations or who were unemployed.…”
Section: Plos Onesupporting
confidence: 87%
See 2 more Smart Citations
“…In fact, whereas clinical recovery improved in both groups, personal recovery improved only in the recent SZ group. In schizophrenia, personal recovery interferes with both symptom reduction and social functioning [ 49 ] and it has been recently found that suicide ideation is less prevalent among individuals with schizophrenia that self-reported greater recovery [ 50 ]. McGlashan [ 51 ] conceptualized the subjective experience of psychosis as a continuum of recovery styles.…”
Section: Discussionmentioning
confidence: 99%